2021
DOI: 10.1002/biof.1761
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Systemic inflammation and oxidative stress induced by inhaled paraquat in rat improved by carvacrol, possible role of PPARγ receptors

Abstract: Control rats were exposed to saline aerosol, two groups were exposed to paraquat (PQ), 27 (PQ-L) and 54 (PQ-H) mg/m 3 aerosols and six groups were treated with carvacrol, 20 (C-L) and 80 (C-H) mg/kg/day, pioglitazone, 5 (Pio-L) and 10 (Pio-H) mg/kg/day, C-L+Pio-L and dexamethasone, 0.03 mg/kg/day, for 16 days after the end of exposure to PQ-H. Different variables were measured after the end of treatment period. Total and differential white blood cells counts, nitrite, malondialdehyde, interleukin (IL)-10, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…The treatment with Zataria multiflora (200 and 800 mg/kg) and carvacrol (20 and 80 mg/kg) improved the inhaled PQ-induced systemic oxidative stress and inflammation ( 75 ). Also, treatment with carvacrol reduced the WBC (total and differential) count, oxidant biomarkers, and inflammatory cytokines, but increased the antioxidants including CAT and SOD, and anti-inflammatory cytokines in the inhaled PQ-exposed rats similar to the effects of pioglitazone and dexamethasone ( 76 ).…”
Section: Resultsmentioning
confidence: 97%
“…The treatment with Zataria multiflora (200 and 800 mg/kg) and carvacrol (20 and 80 mg/kg) improved the inhaled PQ-induced systemic oxidative stress and inflammation ( 75 ). Also, treatment with carvacrol reduced the WBC (total and differential) count, oxidant biomarkers, and inflammatory cytokines, but increased the antioxidants including CAT and SOD, and anti-inflammatory cytokines in the inhaled PQ-exposed rats similar to the effects of pioglitazone and dexamethasone ( 76 ).…”
Section: Resultsmentioning
confidence: 97%
“…The results indicated that treatment with Z. multiflora and carvacrol improved lung inflammation and oxidative biomarkers induced by inhaled PQ, which may indicate the therapeutic potential of the plant and its constituent, carvacrol, in lung inflammation and oxidative biomarkers induced by inhaled PQ (Amin, Roohbakhsh, Memarzia, Kazerani, & Boskabady, 2020). In another similar study, treatment with carvacrol, pioglitazone and dexamethasone also decreased total and differential WBC counts, oxidant markers such as MDA and NO 2 and inflammatory cytokines including IL‐17 and TNF‐ α, but increased antioxidants, including CAT and SOD activities and antiinflammatory cytokines such as IL‐10 and INF‐γ in rats exposed to inhaled PQ (Amin, Memarzia, Kazemi Rad, Shakeri, & Boskabady, 2021).…”
Section: Resultsmentioning
confidence: 82%
“…51 In the lung injury induced by PQ also CAR treatment reduced IL-6 but significantly improved IL-10, and IFN-γ and IFN-γ/IL-6 ratio. 54,55 The results of clinical trials also showed that treatment with CAR for 2 months, significantly reduced inflammatory mediators while increased anti-inflammatory mediators in asthmatic patients 43 and SM-exposed patients. 20,56…”
Section: The Effects Of Car On Inflammatory Mediatorsmentioning
confidence: 98%